Population Trends, Employment Levels, Economic Performance, And Income Evolution in East and West Germany Since Unification - Bedau, Klaus-Dietrich (Journal of Income Distribution®, 1999)
Between 1989 and 1996, former East Germany experienced a population loss of more than 1 million inhabitants as hundreds of thousands of East Germans moved to former West Germany. Population growth in East Germany sank dramatically, since 1955, however, this trend has been reversed and today more children are born than in the preceding year. The number of gainfully employed East Germans shrank between 1989 and 1993 by 3.5 million. Job loss hit female employees, who in East Germany prior to 1989 formed a part of the job force in proportion to their number, especially hard. In 1994 and 1995, employment increased in the East German states, but job growth did not extend into 1996 as economic growth, which sustained a process of “catching up” with West Germany failed to maintain its dynamism. Economic performance disparity between East and West Germany is very large. Although productivity increased significantly in former East Germany, wage costs outran productivity growth. Per Capita income in East Germany in 1991 was 49 per cent of per capital income n West Germany and as of 1994 per capita income had reached 66 per cent of its West German equivalent. Copyright 2000 Elsevier Science Inc. All rights reserved